Differences in Player Position Running Velocity at Lactate Thresholds Among Male Professional German Soccer Players - Schwesig, René; Schulze, Stephan; Reinhardt, Lars; Laudner, Kevin G.; Delank, Karl-Stefan; Hermassi, Souhail (Frontiers in Physiology, 2019)
This study investigated the differences in running velocities at specific lactate thresholds among male German soccer players. One hundred fifty-two professional (3rd league: n=78; 4th league: n=74) male soccer players (mean ± SD; age: 24.7 ± 4.37 years, body mass: 80.8 ± 7.33 kg, body height: 1.83 ± 0.06 m) volunteered for the investigation. Players were categorized as goalkeepers, central defenders, central midfielders, wings and forwards. Players completed a treadmill test, at incremental speeds, to determine running velocity at different blood lactate concentrations (v2=2 mmol/l; v4=4 mmol/l; v6=6 mmol/l). Results indicated that, wings displayed the lowest body mass (76.1 ± 6.06 kg) and body height (1.79 ± 0.06 m). In contrast, goalkeepers were the tallest athletes (1.90 ± 0.03 m), and the heaviest players (86.3 ± 5.08 kg). In addition, the largest difference between positions for running velocity was found at the lactate threshold v2 (p=0.005). The running data revealed that only goalkeepers had significantly lower velocities at the lactate thresholds compared to outfield players. The central midfielders showed the highest average performance level at the lactate thresholds (v2: 12.5 ± 1.20 km/h; v4: 15.2 ± 1.14 km/h; v6: 16.6 ± 1.14 km/h). In conclusion, this study provides soccer and position-specific reference data for the running performance of male professional German soccer players to evaluate the endurance performance in a standardized way. In this context, future research should extend the database for the first and second leagues. Further research assessing running performance during competition matches over the entire season is required to validate the endurance test performance data.